Factors Influencing Job Satisfaction Of Employees In Manufacturing Sector - Dhara Singh; Dr. Sanjeev Kumar; Dr. Manoj Kumar Meet (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Human resources are considered as a key source innovation and updating any system. Therefore, managing human resource is of utmost importance. In an organisation, job satisfaction brings motivation, efficiency and productivity in employees. Every organisation, in all the period, faces to challenge of increase the level of job satisfaction in its employees. For the purpose around eighty research papers and articles related to factors influencing job satisfaction were taken in to consideration. A list of factors influencing job satisfaction were prepared by reading all the above papers. The factors highlighted in the process of analysing the papers were: work-life balance/ job stress, health and safety, company values, recognition, relationship with managers, communication, Salary working condition, and work styles etc. The more frequent factors out of the list were seen as Job stress, Salary and communication. In this research paper these factors were discussed in detailed category wise from thirty of the available research papers in the form of literature review. After analysing the literatures, a proposition is drawn in each category.